Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8mt00091c
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin influences the aggregation of metal-free and metal-bound amyloid-β by direct interaction

Abstract: Proteins from the S100 family perform numerous functions and may contribute to Alzheimer's disease (AD). Herein, we report the effects of S100A8/S100A9 heterooligomer calprotectin (CP) and the S100B homodimer on metal-free and metal-bound amyloid-β (Aβ; Aβ40 and Aβ42) aggregation in vitro. Studies performed with CP-Ser [S100A8(C42S)/S100A9(C3S) oligomer] indicate that the protein influences the aggregation profile for Aβ40 in both the absence and presence of metal ions [i.e., Zn(ii) and Cu(ii)]. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…For S100B this effect has been shown to result from a direct physical interaction with Aβ42 (Cristóvão et al, 2018) and at this stage we can only speculate that similar phenomena might also be occurring for S100A6 and S100A8. In support of this possibility is the evidence that the S100A8-containing heterodimer calprotectin interacts with Aβ40, also influencing its aggregation (Lee et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…For S100B this effect has been shown to result from a direct physical interaction with Aβ42 (Cristóvão et al, 2018) and at this stage we can only speculate that similar phenomena might also be occurring for S100A6 and S100A8. In support of this possibility is the evidence that the S100A8-containing heterodimer calprotectin interacts with Aβ40, also influencing its aggregation (Lee et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…We observed a discrete and novel set of differentially expressed genes that discriminated recovery-phase microglia both from control and from early or late disease. A key feature was upregulation of the calcium-binding heterodimer calprotectin ( S100a8 and S100a9 ), a marker of microglial activity that is elevated in schizophrenia [ 48 ], multiple sclerosis [ 49 ] and Alzheimer’s disease [ 50 ], where it may contribute to amyloidogenesis [ 51 ] and activate TLR4 signalling [ 52 ]. The additional calcium sensors S100a6 and S100a11 were also upregulated during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In PS/APP mice, the S100A8/A9 heterodimer is found to be upregulated in microglial cells surrounding amyloid plaques (Kummer et al, 2012). Additionally, it is reported that S100A8/A9 binds directly to Aβ40 and that it interferes with amyloid formation but no effect was observed over Aβ42 aggregation (Lee et al, 2018). There is also a link between S100A8/A9 and the “non-amyloidogenic” α-secretase ADAM-10, since S100A8/A9 has lower expression in AD mice models overexpressing ADAM-10 (Prinzen et al, 2009).…”
Section: The S100 Protein Familymentioning
confidence: 99%